The Corporate complicity in international crimes in the light of the Rome Statute (regarding the Lafarge Case) - Coteño Muñoz, Alejandro (EUNOMÍA. Revista en Cultura de la Legalidad, 2022)
In line with the recent accusation by the French Justice of the multinational Lafarge and three of its directors for, among other crimes, complicity in war crimes and against humanity due to have negotiated with DAESH, the complicity in international crimes is studied in light of the Rome Statute. Although the criminal liability of legal persons is not recognized by the International Criminal Court, through this analysis it is intended to set up a first basis for the complicity of these companies when negotiating, with the sole purpose of continuing their ordinary production, with different groups in which these international crime are committed, since this practice turns out to be a common place in any armed conflict.
Keywords: complicity; substantial contribution; significant contribution; Lafarge; DAESH